Urate Is a Ligand for the Transcriptional Regulator PecS - Perera, Inoka C.; Grove, Anne (My University, 2010)
PecS is a member of the MarR (multiple antibiotic resistance regulator) family, which has been shown in Erwinia to regulate the expression of virulence genes. MarR homologs typically bind a small molecule ligand, resulting in attenuated DNA binding. For PecS, the natural ligand has not been identified. We have previously shown that urate is a ligand for the Deinococcus radiodurans-encoded MarR homolog HucR (hypothetical uricase regulator) and identified residues responsible for ligand binding. We show here that all four residues involved in urate binding and propagation of conformational changes to DNA recognition helices are conserved in PecS homologs, suggesting that urate is the ligand for PecS. Consistent with this prediction, Agrobacterium tumefaciens PecS specifically binds urate, and urate attenuates DNA binding in vitro. PecS binds two operator sites in the intergenic region between the divergent pecS gene and pecM genes, one of which features two partially overlapping repeats to which PecS binds as a dimer on opposite faces of the duplex. Notably, urate dissociates PecS from cognate DNA, allowing transcription of both genes in vivo. Taken together, our data show that urate is a ligand for PecS and suggest that urate serves a novel function in signaling the colonization of a host plant.
Keywords: MarR, PecS, urate, oxidative burst, plant immunity